EDUKASI KESEHATAN REPRODUKSI DALAM RANGKA MENGHADAPI MENARCHE PADA SISWI DI SD NEGERI SONGKAR - Ana Lestari; Rafi’ah Rafi’ah; Iga Maliga (Pusat Riset dan Inovasi Nasional, 2022)
Lack of knowledge about menstruation can be the cause of long-term reproductive health problems and make young women unprepared for menstruation. Unpreparedness to face menarche causes adolescents to have negative responses such as shame, fear, and worry. Community service activities were carried out in July 2022. The activity was attended by 25 students of class V and VI SD Negeri Songkar. The implementation of community service activities used is the dissemination of reproductive health as a preparation for facing menarche. The method used is the lecture method using leaflets, question and answer method and games/ quizzes. Provision of knowledge about reproductive health to elementary school students needs to be done either as an additional subject or in the form of counseling outside of teaching and learning activities.